The mound-builders - Shetrone, H. C. (Classics in southeastern archaeology., 2004)
A Dan Josselyn Memorial PublicationA classic resource on early knowledge of prehistoric mounds and the peoples who constructed them in the eastern United States. With this accessible volume, Henry Clyde Shetrone made available to general readers the archaeological research data and conclusions concerning the ancient mounds and earthworks that dot the landscape of eastern North America. Dismissing popularly held theories of mysterious giants who built these structures, he explained that their purposes were defensive and ceremonial, that they had been used for habitation, burial, and worship. T.